Factors Affecting Seasoned Corporate Bond Prices - Boardman, Calvin M.; McEnally, Richard W. (Journal of Financial and Quantitative Analysis, 1981)
In this paper prices of corporate bonds are decomposed into elements associated with (1) the pure price of time, (2) the default risk of the agency rating class to which the bond is assigned, and (3) the unique risk and ancillary features of the bond itself.